1992
DOI: 10.1007/bf00877243
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of mitonafide in solid tumors

Abstract: Mitonafide was the first synthetized compound of a new series of 3-nitronaphthalimides with intercalative properties. A phase I study with a conventional escalation scheme was developed. The schedule of drug administration was a daily x 5 days by short (1 h) intravenous (i.v.) infusion, every 21 days. Thirty evaluable patients were treated at doses from 15.4 mg/m2/d x 5 days to 138.6 mg/m2/d x 5 days. The study was interrupted due to appearance of central nervous system toxicity in 5 patients treated at doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…It has been shown earlier that substituted naphthalimides containing N-(2,2-dimethylaminoethyl) chain best represented by Mitonafide [5-nitro group in the aromatic ring] and Amonafide [5-amino group in the aromatic ring] possess significant anti-tumor activities. These have undergone Phase I-II clinical trials with limited results [1,2]. Other types of naphthalimides were also prepared and assessed [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown earlier that substituted naphthalimides containing N-(2,2-dimethylaminoethyl) chain best represented by Mitonafide [5-nitro group in the aromatic ring] and Amonafide [5-amino group in the aromatic ring] possess significant anti-tumor activities. These have undergone Phase I-II clinical trials with limited results [1,2]. Other types of naphthalimides were also prepared and assessed [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Mitonafide was studied in Phase I and II trials, using a short administration schedule (1-h infusion every day x 3-5 d), and it showed activity against solid tumors [19]. However, this dosing schedule was associated with central neurotoxicity.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Phase I clinical trials are currently in progress in Europe and the USA. The absence of a nitro group in the chromophore of elinafide may be advantageous, since the nitro substitution on the monomeric compounds appears to be responsible for the central nervous system toxicity observed in mitonafide clinical trials [19].…”
Section: Biological Activitymentioning
confidence: 99%
“…Chau et al [40] reported that amonafide (xanafide, 14) is neither a substrate nor inhibitor of Pgp. Zhu et al [41] examined the cytotoxicity of amonafide and its derivative R16 (80) in comparison with reference compounds (adriamycin, vincristine and VP16) in three MDRexpressing sublines: K562/A02, MCF-7/ADR and KB/VCR. For each of these cell lines, they calculated the RF as the [42] reported both non-resistant KB3-1 and resistant KB8-5 tumor xenografts in nude mice were highly and equally sensitive to i.v.…”
Section: In Vitro Activitymentioning
confidence: 99%
“…When administered according to a fast infusion schedule: 1h every day for 3 days at 160-180 mg/m 2 /day [79] or every day for 5 days at 15.4-138.6 mg/m 2 /day [80], mitonafide displayed activity against solid tumors but this was accompanied by leukopenia, neutropenia and central neurotoxicity (consisting of severe loss of memory, temporospatial disorientation and high integrative function impairment), while a slow infusion schedule (continuous infusion for 5 days at 107-200mg/m 2 x120h) was safe but devoid of significant activity [81].…”
Section: Human Toxicology-phase I Clinical Trialsmentioning
confidence: 99%